Hasil Belajar Siswa Berdasarkan Gaya Belajar Berbeda pada Pembelajaran Daring Mata Pelajaran PAI di Sekolah Dasar - Almi Novita; Luluk Wulandari; Evi Fatimatur Rosydiyah; Ariandi Ariandi (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2022)
Abstract: Since the entry of Covid-19 into Indonesia, the government has encouraged the public to carry out all activities from home, including teaching and learning activities or study from home (SFH). This situation requires a teacher to be able to design a learning strategy using various online learning media that can support the student learning process, because the right learning media and in accordance with the student's learning style will make it easier for students to achieve their learning targets. This study aims to determine the learning styles and student learning outcomes as well as the influence of learning styles on student learning outcomes in Islamic Education subject class 4-F at Al-Hikmah Elementary School Surabaya. After doing the analysis using Linear Regression Test, this study shows that learning style has a significant influence on student learning outcomes. The results of this study showed that 77% or 23 students had a visual learning style and 23% or 7 students had an auditory learing style and there were no students with a kinestethic learning style. Thus the Islamic Religious Education teachers can teach according to students learning styles, because the learnig process that pays attentions to students learning styles will have a greater influence in improving student learning outcomes in Islamic Religious Education subject.